Canadian entomopathogenic nematode isolates: virulence against black cutworm (Lepidoptera: Noctuidae) - Bélair, Guy; Simard, Louis; Dionne, Julie (Phytoprotection, 2013)
The virulence of ten indigenous and two commercial isolates of entomopathogenic nematodes against the black cutworm, Agrotis ipsilon, was assessed under laboratory conditions. When comparing commercial isolates, Steinernema carpocapsae exhibited higher virulence than S. feltiae. One indigenous isolate of S. carpocapsae (6Sc) provided similar or higher virulence than the commercial isolate against black cutworm larvae. An indigenous strain of S. kraussei demonstrated low virulence in our study.